PROBLEMATIC ISSUES AND SOLUTIONS TO THE USE OF FAIRY TALES IN THE EDUCATION OF CHILDREN AND STUDENTS - Abdullayev Akmal Nasriddinovich; Karimov Islomjon Isroiljon o`g`li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Moral maturity of young people, who are becoming the leading force of society’s life, in today’s rapidly changing educational and ideological views, poses important tasks for modern education systems in many ways. Realizing that manuals and works of art, which are used as educational tools, should be adapted to the needs of the times and improved, important research works are being conducted on them. This article talks about a number of problems encountered in improving the morals of the young generation through fairy tales and their characters, and their solutions.